The Use of Video and TPR to Improve Students’ Vocabulary Mastery - Rizky Lutviana; Siti Mafulah (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2017)
Teaching Junior High School students required fun and interactive activities, yet current practice in teaching them mostly focused on drilling activities, which are monotonous. This study employed Classroom Action Research (CAR), which is aimed at implementing video and TPR (Total Physical Response) teaching technique to improve students’ vocabulary mastery. The subject of this research was 31 first grades of Junior High School students in English vocabulary class. The vocabulary lesson was presented in the form of interactive video in which required students to do vocabulary exercise while singing and moving their body. This research was successfully implemented in 2 cycles. On the Cycle 1, the criteria of success have not been achieved since only 45% students got score 75 or above. Students needed more exercises to understand the materials deeper. On the Cycle 2 students’ score improved, 77.4% students got score 75 or above. Additionally, 82.21% students showed positive attitude toward the technique. Based on the findings it could be concluded that video and TPR teaching technique could improve students’ vocabulary mastery. To implement this technique successfully teacher needs to manage carefully students to be discipline if they are too enthusiastic. Besides, teacher needs to consider the proportion of vocabulary exercise.